Human Bone Marrow Mesenchymal Stromal Cells Promote Bone Regeneration in a Xenogeneic Rabbit Model: A Preclinical Study - Juan Francisco Blanco; Jesús García-Briñon; Lorena Benito-Garzón; David Pescador; Sandra Muntión; Fermín Sánchez-Guijo (Stem Cells International)
Significant research efforts have been undertaken during the last decades to treat musculoskeletal disorders and improve patient’s mobility and quality of life. The goal is the return of function as quickly and completely as possible. Cellular therapy has been increasingly employed in this setting. The design of this study was focused on cell-based alternatives. The present study aimed at investigating the bone regeneration capacity of xenogeneic human bone marrow-derived mesenchymal stromal cell (hMSC) implantation with tricalcium phosphate (TCP) granules in an immunocompetent rabbit model of critical-size bone defects at the femoral condyles. Two experimental groups, TCP and hMSC + TCP, were compared. Combination of TCP and hMSC did not affect cell viability or osteogenic differentiation. We also observed significantly higher bone regeneration in vivo in the hMSC + TCP group, which also displayed better TCP osteointegration. Also, evidence of hMSC contribution to a better TCP osteointegration was noticed. Finally, no inflammatory reaction was detected, besides the xenotransplantation of human cells into an immunocompetent recipient. In summary, hMSC combined with TCP granules is a potential combination for bone regeneration purposes that provides better preclinical results compared to TCP alone.